Challenges in charge preparation and combustion in homogeneous charge compression ignition engines with biodiesel: A review - V. D. Chaudhari; D. Deshmukh (Energy Reports, 2019)
Homogeneous charge compression ignition (HCCI) engines have high efficiency and lower NOx-soot emissions than diesel and gasoline engines. However, these engines suffer from high HC, CO and unregulated emissions and combustion phasing control. The fuel chemistry, charge dilution and fuel injection timing strongly control HCCI combustion. The oxygenated renewable biofuels, such as biodiesel and alcohol, can be used to control combustion. The use of laser diagnostic techniques can provide insight into the combustion chamber for the air-fuel charge formation and combustion studies. The charge stratification achieved using intake air conditioning, dilution or varying the fuel reactivity can overcome the challenges associated with HCCI engines. The review paper examine the critical challenges in the HCCI engine, use of the renewable fuels and their impact on engine-out emissions.
Keywords: 330; Combustion phasing; HCCI; OH radicals; Optical diagnostics; Reactivity; Stratification